Optimasi Proses Fermentasi Semi Padat Onggok Singkong Menggunakan Metode Response Surface Methodology (RSM) - Beni Hidayat; Udin Hasanudin; Muhammad Muslihudin; Syamsu Akmal; Siti Nurdjanah; Neti Yuliana (Politeknik Negeri Lampung., 2021)
The application of semi-solid fermentation has been able to increase the potential for using cassava pulp, an underused biomass from starch processing (tapioca), as foodstuffs which are reflected in an increase in protein content up to 7.07% and a decrease in cyanide content to less than 10 mg/kg (8.78 mg/kg). Further process optimization is required if the cassava pulp fermentation process is to be carried out on an industrial scale. This research was aimed to obtain the optimal fermentation process parameters to produce cassava pulp flour with optimal characteristics as foodstuffs. Optimization of the fermentation process was carried out using the Response Surface Methodology (RSM) with the Central Composite Design model. There were three optimized factors, namely the concentration of S. cerevisiae (1%-3%), ammonium sulfate concentration (1%-2%), and fermentation time (72-120 hours). The determination of the upper and lower limits was based on preliminary research. The optimal characteristics of fermented cassava pulp flour is obtained in the process parameters: starter concentration 1.67%, ammonium sulphate concentration 1.00%, and fermentation time 77.65 hours. The optimal process parameters will produce fermented cassava pulp flour with a protein content of 6.17%, cyanide content of 8.64 mg/kg, and an odour score of 4.93 (maximum score of 5, like very much) which is very potential to be used as foodstuffs.